The Effect of Total Assets Turnover on Pharmaceutical Companies Profit Growth listed on the Indonesian Stock Exchange - Dwiningsih, Sri; Sukariyono, Dedi; Putri, Inneke Dimas (Institut Teknologi dan Bisnis Widya Gama Lumajang, 2024)
The author's aim is to determine the effect of total asset turnover on pharmaceutical companies profit growth listed on the Indonesian Stock Exchange. The methods used by the author in conducting this research are the descriptive analysis method and multiple linear regression analysis. Data processing was carried out using IBM SPSS Statistics 25. This study population was all pharmaceutical companies listed on the Indonesian Stock Exchange in 2020–2022, with the number of samples taken according to the researcher's criteria of 10 pharmaceutical companies. Partial research results show that the Total Assets Turnover variable has a significant effect on profit growth in pharmaceutical companies. In the determination test, the adjusted R square result was 0.168, which means that 16.8% of the independent variable (X) consisting of Total Assets Turnover/TATO (X) can explain the dependent variable, namely profit growth (Y), and the remaining 83.2% is influenced by other factors that are not explained by this research.